Pathogenetic Mechanisms of Liver Damage in Toxic Hepatitis - Sayfutdinova Z.A; Muhammadiev X.G; Xashimova G. T; Yusupov B.N (Genius Journals, 2022)
The aim of this study is to prepare an updated list of drugs that cause hepatotoxicity and to identify drugs that, according to scientific data, are most likely to cause hepatotoxicity. Some aspects of hepatotoxic drugs are like manifestation of hepatotoxicity, type of injury, mechanisms of hepatotoxicity, risk factors and clinical manifestations. Three categories were established to assess the likelihood of hepatotoxicity and the type of injury: certain, probable, and possible. The list is made up of 181 drugs and 17 combination dosage forms or therapeutic regimens that can cause hepatotoxicity. Of these, methotrexate, minocycline, vancomycin, everolimus, isoniazid, and tamoxifen are categorized as certain probabilities.In conclusion, over 180 hepatotoxic drugs were identified, of which six were categorized as certain probabilities and most were categorized as possibilities. Summarizing the information shows that various categories of drugs can cause toxic effects on the liver
Keywords: hepatotoxicity; hepatitis; liver damage; risk factors;